2001
DOI: 10.1007/s00266-001-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Body Image in Cosmetic Surgery Patients

Abstract: The purpose of this study was to investigate the presence of psychiatric symptoms and evaluate the perceptive, cognitive, and behavioral aspects of body image in cosmetic surgery patients. These parameters of 20 cosmetic patients and of 20 control patients matched for age, gender, education, and marital status who attended the general surgery department for minor surgery were compared in a cross-sectional design. Symptom Check List-90 (SCL-90), Beck Depression Inventory (BDI), and The Multi-Dimensional Body Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Scores > 10 are considered positive for depression. The BDI has been used in numerous studies with general and cancer populations[2324] with satisfactory reliability ranges from 0.73 to 0.92[25] and validity range from 0.62 to 0.66. [26]…”
Section: Methodsmentioning
confidence: 99%
“…Scores > 10 are considered positive for depression. The BDI has been used in numerous studies with general and cancer populations[2324] with satisfactory reliability ranges from 0.73 to 0.92[25] and validity range from 0.62 to 0.66. [26]…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing need for awareness of this disorder among professionals who perform cosmetic medical procedures, as nonpsychiatric treatments are generally not considered beneficial for these patients. [24][25][26][27] Currently no information exists regarding BDD prevalence and characteristics among dermatologic patients in Brazil. Moreover, very few studies have evaluated BDD prevalence after the latest procedures were approved.…”
mentioning
confidence: 99%
“…Level of insight may vary; the specifi ers used to describe insight regarding beliefs about appearance are good/fair, poor, and delusional/absent. The poor insight specifi er is most commonly used in BDD (Vargel and Ulusahin 2001 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Gender distribution appears to be equal across the globe; for example, 2.2 % of males and 2.5 % of females in the USA (Koran et al 2008 ); and 1.4 % of males and 1.9 % of females in Germany (Buhlmann et al 2010 ;Koran et al 2008 ). The prevalence rate of BDD differs across settings; however, studies in clinical samples report a prevalence of 9-12 % among dermatology patients and 3-53 % among cosmetic surgery patients, 8-37 % among OCD patients, 11-13 % among social anxiety disorder patients, and 26 % among individuals with HPD (Aouizerate et al 2003 ;Brawman-Mintzer et al 1995 ;Castle et al 2004 ;Hollander et al 1993 ;Ishigooka et al 1998 ;Perugi et al 1997 ;Phillips et al 1996Phillips et al , 2000Sarwer et al 1998 ;Uzun et al 2003 ;Vargel and Ulusahin 2001 ;Vindigni et al 2002 ). In adolescent samples, prevalence rates ranging between 6.7 and 14 % in psychiatric inpatient settings (Phillips and Rogers 2011 ) and 2.2 % in high school settings (Mayville et al 1999 ) have been reported.…”
Section: Epidemiologymentioning
confidence: 99%